Importance of FaWRKY71 in Strawberry (Fragaria × ananassa) Fruit Ripening - Maolan Yue; Leiyu Jiang; Nating Zhang; Lianxi Zhang; Yongqiang Liu; Yan Wang; Mengyao Li; Yuanxiu Lin; Yunting Zhang; Yong Zhang; Ya Luo; Xiaorong Wang; et al. (2022)
WRKY transcription factors play a nonnegligible role in plant growth and development, but little is known about the involvement of WRKY transcription factors in the regulation of fruit ripening. In this study, FaWRKY71 was identified to be closely related to fruit maturation in octoploid strawberry. FaWRKY71 protein localized in the nucleus and responded to cold, salt, low phosphate, ABA, and light quality in strawberry seedlings. The temporal and spatial pattern expression analysis indicated that FaWRKY71 was expressed in all the detected tissues, especially in the full red fruits. In addition, FaWRKY71 gave rise to the accumulation of anthocyanin content by promoting the expression of structural genes FaF3'H, FaLAR, FaANR, and transport factors FaTT19 and FaTT12 in the flavonoid pathway, and softening the texture of strawberry via up-regulating the abundance of FaPG19 and FaPG21. Furthermore, FaWRKY71 was a positive regulator that mediated resistance against reactive oxygen species by enhancing the enzyme activities of SOD, POD, and CAT, reducing the amount of MDA. Altogether, this study provides new and comprehensive insight into the regulatory mechanisms facilitating fruit ripening in strawberry.